Towards an Integrated Maturity Model of Asset Management Capabilities - Mahmood, M.; Dhakal, S.; Wiewiora, A.; Keast, R.; Brown, Kerry (Springer, 2015)
Asset service organizations often recognize asset management as a core competence to deliver benefits to their business. But, how do organizations know whether their asset management processes are adequate? Asset management maturity models, which combine best practices and competencies, provide a useful approach to test the capacity of organizations to manage their assets. Asset management frameworks are required to meet the dynamic challenges of managing assets in contemporary society. Although existing models are subject to wide variations in their implementation and sophistication, they also display a distinct weakness in that they tend to focus primarily on the operational and technical level and neglect the levels of strategy, policy, and governance as well as the social and human resources—the people elements. Moreover, asset management maturity models have to respond to the external environmental factors, including climate change and sustainability, stakeholders, and community demand management. Drawing on five dimensions of effective asset management—spatial, temporal, organizational, statistical, and evaluation—as identified by Amadi-Echendu et al. [1], this paper carries out a comprehensive comparative analysis of six existing maturity models to identify the gaps in key process areas. Results suggest incorporating these into an integrated approach to assess the maturity of asset-intensive organizations. It is contended that the adoption of an integrated asset management maturity model will enhance effective and efficient delivery of services.